A molecular framework for the embryo growth in germinating seeds of Solanum lycocarpum A. St.-Hil., a nurse plant species - Silveira, Lilian E. D. [UNESP]; Ribeiro-Oliveira, João Paulo; Ajala-Luccas, Daiani [UNESP]; Bravo, Juliana P. [UNESP]; da Silva, Edvaldo A. A. [UNESP] (Wiley, 2019)
We are clarifying how the functional embryo growth occurs in germinating seeds of Solanum lycocarpum A. St.-Hil., a nurse plant with a central role in forest dynamics in the Cerrado (a biodiversity hotspot). For that, we used classical seed germination measurements (germinability, mean germination time, mean germination rate, coefficient of variation of the germination time, synchronisation index and germination time range) and gene expression of mRNA codifying key proteins/enzymes for the success in the seed–seedling transition (Cyclin, Actin, Small Heat Shock Protein, Glutathione S-transferase, Malate Dehydrogenase, Alcohol Dehydrogenase). Our findings demonstrate: (a) Although germination kinetics in S. lycocarpum seeds is slower than that in tomato seeds, the fold change of genes codifying key enzymes for the embryo development is similar in germinating seeds of both species. (b) The genes used here are useful, from a technical point of view, for classifying commercial seed samples of the species in relation to physiological quality. More notably, cyclin and malate dehydrogenase genes have a greater expression, both in germination sensu stricto and in immediate post-germination. (c) A molecular framework for the embryo growth in germinating seeds of S. lycocarpum can be a functional explication for the species to be a nurse plant. Thus, the overlapping of classical and contemporary measurements is especially interesting to those species playing a central role in the environment, such as nurse plants, and may represent a new conservationist paradigm.
Keywords: Cerrado; growth and development; native forest species; seed germination; seed metabolism